Longing in Buah Rindu, a Collection of Poems by Amir Hamzah: A Ferdinand de Saussure Semiotic Analysis: Kerinduan dalam Kumpulan Puisi Buah Rindu Karya Amir Hamzah: Analisis Semiotika Ferdinand de Saussure - Suhairiyah Suhairiyah; Sitti Fatimatul Azzahro; Nayla Chinta Prilisia; Fajar Ariyanto; Atiqotul Fitriyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the representation of longing in three selected poems from Buah Rindu by Amir Hamzah (Cempaka, Buah Rindu, and Sunyi) using Ferdinand de Saussure's semiotic approach. Employing a descriptive qualitative method with purposive sampling, the analysis focuses on the structural relationship between the signifier, represented by the linguistic forms of the poems, and the signified, represented by the underlying concepts of meaning, to reveal the multilayered dimensions of longing embedded in the texts. The findings demonstrate that Amir Hamzah does not construct longing as a single or homogeneous concept. Instead, the sign system in the three poems operates within two interconnected domains: emotional longing rooted in human relationships and spiritual longing reflecting a Sufi aspiration toward God. In Cempaka, the cempaka flower functions as a signifier of sensual and romantic longing directed toward a beloved. In Buah Rindu, the figures of the mother and the moment of birth at dawn serve as signifiers that extend beyond familial affection to symbolize humanity's sacred origin (fitrah) and the soul's yearning to return to the Creator. In Sunyi, the physical presence of the beloved, which fails to alleviate the lyrical speaker's inner emptiness, marks the point at which human love transforms into transcendental solitude. These findings provide a new analytical perspective on the application of Saussurean semiotics to modern Indonesian Sufi poetry and demonstrate that Buah Rindu should not be interpreted merely as a collection of romantic and melancholic poems, but as a sophisticated system of signs encoding the spiritual anxiety and existential longing of the human soul.